The Meaning, Prospects, and Future of the Commons: Revisiting the Legacies of Elinor Ostrom and Henry George. (March 2016) - Obeng‐Odoom, Franklin
Abstract: Elinor Ostrom's work on the commons has convinced mainstream economists that "collective" governance of the commons can overcome the "tragedy of the commons" and "free‐rider problems." Yet, a more systematic appraisal of Ostrom's work shows that it contains no concept of justice. Her idea of rights is extremely limited, often tied to the notion of joint, rather than equal, rights. Indeed, for Ostrom, the notion of the commons is socially separatist and not ecological. Ostrom uses historical examples, but without analyzing how common possession historically evolved and was undermined by external forces. Hence her proposed "collective action" to save the commons actually accelerates the real threats to the commons. A strikingly different and more holistic approach to the commons is offered by Henry George, who posits the commons as the most important path to social, economic, and ecological sustainability. Unlike Ostrom, who studied the commons "scientifically" to show that some goods are neither private, public, nor club‐based, George studied the commons to understand and remove injustice at the roots. His approach is more critical and certainly more relevant today in showing that another world is possible. However, George's work too, requires significant changes to update its framing of the meanings, prospects, and future of the commons.